A study to evaluate the impact of training in improving knowledge of health care workers regarding bio-medical waste management in a tertiary care hospital - Thakan, Somya; Dhaundiyal, Ankita; Katiyar, Shruti (International Journal Of Community Medicine And Public Health, 2025)
Background: Biomedical waste (BMW) poses a significant health hazard, especially for healthcare workers directly involved in its generation and handling. Inadequate knowledge and poor practices often result in occupational exposure and environmental risks. This study aimed to assess the impact of structured BMW management training on knowledge and practices among hospital staff in three healthcare facilities in Rajasthan - General, Janana, and Covid Hospitals. Methods: A total of 156 participants including staff nurses, laboratory technicians, housekeeping staff, and class 4/ward boys were recruited through convenience sampling and trained in batches over one week. A pre- and post-training knowledge assessment (maximum score: 20) was conducted. Self-reported practices and attitudes were also evaluated using a structured questionnaire. Results: The mean knowledge score significantly improved from 9.2±2.8 (pre-test) to 16.4±2.1 (post-test) (p<0.001). The greatest improvement was observed among Class 4 staff and housekeeping personnel. Post-training, self-reported compliance with appropriate BMW segregation rose from 62% to 94%, use of PPE from 69% to 96%, and hand hygiene after waste handling from 72% to 93%. Conclusions: The training program led to a significant improvement in both knowledge and self-reported practices regarding BMW management across all categories of hospital staff. Targeted, context-specific training can play a crucial role in strengthening hospital waste management systems, particularly in resource-constrained settings. The model used in this study is scalable and can be adopted across similar healthcare institutions.